Design and verification of the onboard 6G core network architecture and network functions - WANG Shangguang; WANG Chao; MA Xiao; XING Ruolin; ZHOU Ao (Dianxin kexue)
In order to comprehensively improve the in-orbit service capability of satellite networks, it is necessary to integrate 6G core networks and satellite networks. In view of the urgent need of 6G core networks deployment， the system architecture of the onboard 6G core network was designed, including distributed architecture, offline autonomy, intelligent network elements and so on. The network elements of the onboard 6G core network were optimized, including access and mobility management, session management, distributed service registration and discovery, etc. The effectiveness of the proposed 6G core network architecture was verified by the on-orbit deployment and simulation tests. The simulation results show that the average communication delay between network functions of the centralized onboard 5G core network is 109.3 ms, while the value of the distributed onboard 6G core network is 60.3 ms, which is a 44.8% reduction in comparison. In addition, the average delays of 5G centralized service registration and service discovery are 40.53 ms and 40.04 ms respectively, while the average delays of 6G distributed service registration and service discovery are 35.18 ms and 34.91 ms respectively, with average reductions of 13.2% and 12.8% respectively.